If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -3(4 + -2x) = 4(x + -3) 5 + (4 * -3 + -2x * -3) = 4(x + -3) 5 + (-12 + 6x) = 4(x + -3) Combine like terms: 5 + -12 = -7 -7 + 6x = 4(x + -3) Reorder the terms: -7 + 6x = 4(-3 + x) -7 + 6x = (-3 * 4 + x * 4) -7 + 6x = (-12 + 4x) Solving -7 + 6x = -12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -7 + 6x + -4x = -12 + 4x + -4x Combine like terms: 6x + -4x = 2x -7 + 2x = -12 + 4x + -4x Combine like terms: 4x + -4x = 0 -7 + 2x = -12 + 0 -7 + 2x = -12 Add '7' to each side of the equation. -7 + 7 + 2x = -12 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = -12 + 7 2x = -12 + 7 Combine like terms: -12 + 7 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5
| 50x=2.99 | | 4/7=n/12 | | x^2+8x(.5)=10 | | 3/4x-11=7 | | 4d=12 | | (x-6)+72=180 | | -12x=-4x^2+16 | | 7+2/5x | | (x-5)+132=180 | | 2(c-7)=6(c+1)+4c | | 7x^7y^5+63x^5y^4+35xy=0 | | -3.6x=1.2 | | -4(a-2)=10 | | 1/5n+3=6 | | (7x-9)-3(2x+1)=-5 | | 5x-(x-3)+2=7(2x+1)(x+4)-16 | | (1/n+3)+(5/n^2-9)=(2/n-3) | | 5a+10=60 | | 4x+3-2x=10 | | -6(4n+6)=5n-17 | | 20x-2.8=25.16 | | 3n*3n=12 | | -6+3+(-4)= | | x^2+3x=-333/4 | | 4x-12=7x-36 | | 3y-4=-2y-14 | | 3n+3n=12 | | 4x-12=7x-46 | | -t=0.4-3 | | 3.5(j+2)=1.4(16+j) | | 3=(m+2) | | A-5=-2 |